Acute changes in morphology and renal vascular relaxation function after renal denervation using temperature-controlled radiofrequency catheter - Su, Enyong (BMC Cardiovasc Disord, 2019)
BACKGROUND: Resistant hypertension and renal sympathetic hyperactivity are closely linked, and catheter-based renal denervation (RDN) is regarded as a new treatment strategy. However, the acute changes in vascular morphology and relaxation function have yet to be evaluated, and these may be important for the efficacy and safety of the procedure. In this study, we explored these questions by conventional temperature-controlled cardiac radiofrequency catheter-based RDN in a pig model. METHODS: Six mini-pigs were randomly divided into the renal denervation (RDN) group (n = 3) and the Sham-RDN group (n = 3). Animals in the RDN group underwent unilateral radiofrequency ablation, and those in the Sham-RDN group underwent the same procedure except for the ablation. The pigs were examined by angiography pre- and post-RDN and were euthanized immediately thereafter. Renal arteries were processed for histological and molecular biology analyses as well as for in vitro vascular tension testing. RESULTS: Compared with the Sham-RDN group, the RDN caused vascular intima and media injury, renal nerve vacuolization, mild collagen fiber hyperplasia and elastic fiber cleavage (all p < 0.05). The RDN group also significantly exhibited nitric oxide synthase pathway inhibition and decreased endothelium-independent vascular relaxation function Compared to the Sham-RDN group (all p < 0.05). CONCLUSIONS: In this porcine model, renal artery denervation led to vascular wall injury and endothelial dysfunction in the acute phase, which negatively affected vascular relaxation function. Thus, this process may be detrimental to the prognosis and progress of hypertension patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12872-019-1053-z) contains supplementary material, which is available to authorized users.